Keefektifan Metode Bercerita Untuk Meningkatkan Kemampuan Berbahasa Pada Siswa Di SMP Pancasila 3 Baturetno - Yasmin Faisa Shofian (Buletin Pengembangan Perangkat Pembelajaran, 2023)
This research discusses the application of the storytelling method in improving students' language skills at SMP Pancasila 3 Baturetno. Before implementation, the level of students' language skills was measured through a pretest, while factors influencing language skills were identified through interviews and classroom observations. After the storytelling method intervention, the posttest showed a significant increase in students' language skills. These findings confirm the effectiveness of the storytelling method as a tool capable of stimulating students' language understanding and expression. Apart from improving language skills, the storytelling method also has a positive impact on students' motivation, self-confidence and interest in language learning. Students are actively engaged and confident in communicating, creating a dynamic and participatory learning environment. The implications of this research stimulate consideration for integrating storytelling methods in curriculum design and language learning practices at the junior high school level. Thus, this research contributes to the understanding of the storytelling method as an innovative strategy in developing students' language skills